Peningkatan Efektifitas Dan Efisiensi Pada Sistem Pelelangan Secara Elektronik (SPSE) Di Kabupten Jombang - Khoiruddin; Afif Alfiyanto (Journal of Public Power, 2022)
The purpose of this study was to determine the role of the Government of Jombang Regency in increasing the effectiveness and efficiency of public services regarding the procurement of goods and services through the Electronic Procurement System (SPSE). This research is a survey research on secondary data related to Jombang Regency Public Service. with a socio-legal approach method, analysis is the process of compiling data is qualitative analysis. The results of this study indicate that LPSE in providing services to the community has a positive impact on the community. The implementation of the right procurement strategy will produce goods/services with the right quality, right quantity, right time, right source, and right price, based on the rules/procedures, ethics, policies and principles of procurement. The right strategy will create an efficient procurement implementation which is characterized by: Lower administrative costs; The purchase price is close to the market price; Fewer number of procurement packages; Procurement method using electronic tools; The scope of procurement that is part of the organization's strategy; and strategic implementation.